(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This scientific article explores the critical aspects of safe driving in challenging road conditions, emphasizing the importance of driver preparedness, vehicle technology, and road infrastructure. The discussion encompasses adverse weather conditions, poor road surfaces, and other challenging situations that necessitate heightened driver awareness and adaptive driving techniques. By examining the interplay of these factors, this article aims to contribute to the ongoing efforts in improving road safety and reducing accidents in difficult driving conditions.